2006
DOI: 10.1002/elsc.200620165
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Traits and Enzyme Form Patterns of (R)‐2‐(2,4‐Dichlorophenoxy)propionate/α‐Ketoglutarate Dioxygenase (RdpA) after Expression in Different Bacterial Strains

Abstract: The rdpA gene of strains Delftia acidovorans MC1, Rhodoferax sp. P230, and Sphingobium herbicidovorans MH proved to be identical. However, when RdpA [(R)‐2‐(2,4‐dichlorophenoxy)propionate/α‐ketoglutarate dioxygenase] was investigated after purification from the various strains, significant differences in the kinetics and some chemical properties of the enzymes were observed. The preference for substrates ranged in the order (R)‐2‐(2,4‐dichlorophenoxy)propionate (2,4‐DP) > (R)‐2‐(4‐chloro‐2‐methylphenoxy)pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In addition, they are characterized by very fast adaptation to a given cultivation technique. The weeds collected during harvest can also carry bacterial, viral or fungal diseases, and can thus be harmful to humans and animals . Therefore application of herbicides is a common necessity with no other alternative.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are characterized by very fast adaptation to a given cultivation technique. The weeds collected during harvest can also carry bacterial, viral or fungal diseases, and can thus be harmful to humans and animals . Therefore application of herbicides is a common necessity with no other alternative.…”
Section: Introductionmentioning
confidence: 99%
“…The best described are Sphingomonas herbicidovorans MH (16,48) and Delftia acidovorans MC1 (28,29), from which rdpA and sdpA genes were first isolated and sequenced (30,39). Enzyme activity from these strains has shown that RdpA dioxygenase is generally highly specific to the R enantiomer of 2-phenoxypropionates and shows very weak activity toward phenoxyacetates, whereas SdpA is enantioselective to the S enantiomer but can also convert certain phenoxyacetates such as 2,4-D and MCPA with various catalytic activities (27,31,44,45). The genetic background has only recently become available and shows that rdpA sequences reported to date are nearly identical while sdpA sequences between S. herbicidovorans MH and D. acidovorans MC1 are far more variable (30,39).…”
mentioning
confidence: 99%
“…The basal 2,4-D consumption (Tables 1 and 2) can be explained by some catalytic activity of RdpA with 2,4-D [5,10] and consequently wash-in of 2,4-D into chemostat cultures growing on (R)-2,4-DP proceeded to stationary 2,4-D concentrations well below those in the feeding solution (Fig. 1).…”
Section: Adaptation Resulting In Faster 24-d Degradationmentioning
confidence: 94%
“…P230 were 2-5 times lower for all phenoxyalkanoates than those of RdpA derived from the other two strains. Moreover, the K m values of strain P230 for phenoxyacetates were more similar to those for (R)-phenoxypropionates [10]. These differences correlated with the appearance of multiple forms of RdpA, resulting from posttranslational modification, which became visible after separation in 2D gels [10,11].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation